10th IET International Conference on Developments in Power System Protection (DPSP 2010). Managing the Change 2010
DOI: 10.1049/cp.2010.0344
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive protection system for distribution networks with distributed energy resources

Abstract: This paper deals with the concept development and laboratory testing of an adaptive protection system for distribution networks with distributed energy resources. Adaptation of protection relay settings according to currently available short-circuit current at respective grid nodes, is one solution to cope with the challenges originating from distributed generation. The challenges in conventional protection systems in low and medium voltage grids are discussed and a new concept of an adaptive network overcurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 4 publications
0
35
0
1
Order By: Relevance
“…A Smart Electric Grid can identify where electricity is lost or where the system is not in balance or optimized. Such optimization can save 3% or more of overall electric demand without requiring any change in consumer behavior [65].…”
Section: Smart Grid Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…A Smart Electric Grid can identify where electricity is lost or where the system is not in balance or optimized. Such optimization can save 3% or more of overall electric demand without requiring any change in consumer behavior [65].…”
Section: Smart Grid Systemmentioning
confidence: 99%
“…has accelerated the transition towards greener energy sources. Keeping in view the aforementioned challenges of integrating renewable energy sources to the grid, some of the possible ways for renewable energy utilization in a grid are [65]:…”
Section: Managing Renewable Energy In a Gridmentioning
confidence: 99%
“…the mal-tripping of a healthy feeder due to reverse currents caused by a fault on an adjacent feeder and the blinding effect i.e. the failure or delayed operation of protection relays due to reduced fault current seen at the start of the feeder [1][2]. There are many solutions suggested in literature to account for these problems, for example: In [3], the authors propose to solve the blinding effect by changing the relay settings during the planning stage.…”
Section: Introductionmentioning
confidence: 99%
“…A very appealing approach to safely accommodate increasing levels of DGs consists in adapting the protection relay settings with the changing operating conditions of the network [2] [6]. Identifying the changes in operating conditions, (mainly the status of the DGs) is a challenging task as nowadays most distribution systems are poorly observable.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the studies in [41][42][43][44][45][46][47] suggested the adaptive protection scheme considering several types of relays (distance relays, OCRs, etc. ), also considering grid-connected and islanded mode of operations.…”
mentioning
confidence: 99%